CAREER INDECISION INTERVENTION: A SYSTEMATIC LITERATURE REVIEW - Fitri, Indrya; Hidayat, Dede Rahmat; Wahyuni , Eka (LP2M IAI Al-Khairat Pamekasan, 2025)
This study was conducted to examine and analyze various interventions related to career indecision so that it can serve as a reference for career counselors in applying appropriate interventions. This study employed a systematic literature review (SLR) methodology following the PRISMA guidelines, which include identification, screening, and inclusion. Data were collected over the past five years (2020–2025) through the Google Scholar, Scopus, and ScienceDirect databases, yielding 1,135 data points, which were then screened to produce nine articles for review. The results of the analysis show that there are several effective interventions to overcome career uncertainty, including Online Career Development Program (OCDP), Life Design Counseling, Solution-Focused Brief Career Group Counseling), and classroom-level interventions.